SNAP and Paycheck Cycles. (26th April 2019) - Beatty, Timothy K. M.; Bitler, Marianne P.; Cheng, Xinzhe Huang; van der Werf, Cynthia
Abstract : It is well documented that individuals do not spend the Supplemental Nutrition Assistance Program (SNAP) benefits smoothly over the month after receipt. Rather, recipients spend a disproportionate share of benefits at the beginning of the benefit month. This has costs for recipients and stores. There is also evidence that other income streams, such as Social Security and paychecks, are not spent smoothly. The presence of these other income streams may bias estimates of the effects of this SNAP cycle on consumption for working SNAP beneficiaries and those who receive other government benefits. We use data from United States Department of Agriculture's National Household Food Acquisition and Purchase Survey to explore how the SNAP cycle is affected by accounting for these other income streams. We find suggestive evidence that the cycle is more pronounced for workers who are paid on a weekly or monthly basis, but little evidence that cycles in other income streams mitigate or exacerbate the SNAP cycle.